Carbon footprint of atrial fibrillation catheter ablation. Issue 2 (15th September 2022) - Ditac, Geoffroy; Cottinet, Pierre-Jean; Quyen Le, Minh; Grinberg, Daniel; Duchateau, Josselin; Gardey, Kévin; Dulac, Arnaud; Delinière, Antoine; Haddad, Christelle; Boussuge-Roze, Julie; Sacher, Frédéric; Jaïs, Pierre; et al.
Abstract: Aims: Climate change represents the biggest global health threat of the 21st century. Health care system is itself a large contributor to greenhouse gas (GHG) emissions. In cardiology, atrial fibrillation (AF) catheter ablation is an increasing activity using numerous non-reusable materials that could contribute to GHG emission. Determining a detailed carbon footprint analysis of an AF catheter ablation procedure allows the identification of the main polluting sources that give opportunities for reduction of environmental impact. To assess the carbon footprint of AF catheter ablation procedure. To determine priority actions to decrease pollution. Methods and results: An eco-audit method used to predict the GHG emission of an AF catheter ablation procedure was investigated. Two workstations were considered including surgery and anaesthesia. In the operating room, every waste produced by single-use medical devices, pharmaceutical drugs, and energy consumption during intervention were evaluated. All analyses were limited to the operating room. Thirty procedures were analysed over a period of 8 weeks: 18 pulmonary veins isolation RF ablations, 7 complex RF procedures including PVI, roof and mitral isthmus lines, ethanol infusion of the Marshall vein and cavo tricuspid isthmus line, and 5 pulmonary vein isolation with cryoballoon. The mean emission during AF catheter ablation procedures was 76.9 kg of carbon dioxide equivalent (CO2 -e). The operating field accounted for 75.4% of the carbon footprint, while only 24.6% for the anaesthesia workstation. On one hand, material production and manufacturing were the most polluting phases of product life cycle which, respectively, represented 71.3% (54.8 kg of CO2 -e) and 17.0% (13.1 kg of CO2 -e) of total pollution. On the other hand, transport contributed in 10.6% (8.1 kg of CO2 -e), while product use resulted in 1.1% (0.9 kg of CO2 -e) of GHG production. Electrophysiology catheters were demonstrated to be the main contributors of environmental impact with 29.9 kg of CO2 -e (i.e. 38.8%). Three dimensional mapping system and electrocardiogram patches were accounting for 6.8 kg of CO2 -e (i.e. 8.8% of total). Conclusion: AF catheter ablation involves a mean of 76.9 kg of CO2 -e. With an estimated 600 000 annual worldwide procedures, the environmental impact of AF catheter ablation activity is estimated equal to 125 tons of CO2 emission each day. It represents an equivalent of 700 000 km of car ride every day. Electrophysiology catheters and patches are the main contributors of the carbon footprint. The focus must be on reducing, reusing, and recycling these items to limit the impact of AF ablation on the environment. A road map of steps to implement in different time frames is proposed. Graphical Abstract: Graphical Abstract